Post-Frey Procedure Quality of Life in South African Patients with Painful Chronic Pancreatitis - Jeppe, Cara Yvonne; Becker, Piet; Smith, Martin Derrick (JOP. Journal of the Pancreas, 2013)
Context Pre- and post-Frey procedure data assessing quality of life in South African patients with painful chronic pancreatitis were compared using two instruments of measure. Objective The objective was to evaluate the post-Frey procedure quality of life and to evaluate which of the two instruments was most appropriate in such patients. Methods A prospective, observational, longitudinal study using the EORTC QLQ-C30 and a locally developed structured interview was performed. Results Between January 2002, when the QLQ-C30 was introduced, and February 2009, 45 consecutive patients underwent a Frey procedure at the Chris Hani Baragwanath Hospital in Soweto, Johannesburg, South Africa. Thirteen of these patients were lost to follow up. Thirty two participants answered both instruments before and after the procedure. Follow up data were analyzed until June 2009. The mean follow up was 24.8 months ranging from 1 to 83 months. There were clinically relevant improvements in most QLQ-C30 domains and structured interview items at the last post-operative visit. The mean pain levels (VAS 0-10 and QLQ-C30 PA) were significantly reduced post-operatively. Twenty five participants answered both instruments within six months and again later at a minimum of six months after surgery with no significant differences in the overall QLQ-C30 functional (P=0.967) and symptom (P=0.253) scale scores between the two time periods. In general, outcomes measured by the two instruments were similar. Conclusions Although the follow up period was short, results suggest that benefits were mostly made manifest within six months post-operatively and were sustained during the follow up period. The structured interview included a counseling component and locally pertinent issues not addressed in the QLQ-C30 and it is therefore recommended as the instrument of choice in this setting. Image: Chris Hani Baragwanath Academic Hospital. Johannesburg, South Africa